Frequency and types of the medication errors in an academic emergency department in Iran: The emergent need for clinical pharmacy services in emergency departments - Alireza Zeraatchi; Mohammad-Taghi Talebian; Amir Nejati; Simin Dashti-Khavidaki (Wolters Kluwer Medknow Publications, 2013)
Objective: Emergency departments (EDs) are characterized by simultaneous care of multiple patients with various medical conditions. Due to a large number of patients with complex diseases, speed and complexity of medication use, working in under-staffing and crowded environment, medication errors are commonly perpetrated by emergency care providers. This study was designed to evaluate the incidence of medication errors among patients attending to an ED in a teaching hospital in Iran. Methods: In this cross-sectional study, a total of 500 patients attending to ED were randomly assessed for incidence and types of medication errors. Some factors related to medication errors such as working shift, weekdays and schedule of the educational program of trainee were also evaluated. Findings: Nearly, 22% of patients experienced at least one medication error. The rate of medication errors were 0.41 errors per patient and 0.16 errors per ordered medication. The frequency of medication errors was higher in men, middle age patients, first weekdays, night-time work schedules and the first semester of educational year of new junior emergency medicine residents. More than 60% of errors were prescription errors by physicians and the remaining were transcription or administration errors by nurses. More than 35% of the prescribing errors happened during the selection of drug dose and frequency. The most common medication errors by nurses during the administration were omission error (16.2%) followed by unauthorized drug (6.4%). Most of the medication errors happened for anticoagulants and thrombolytics (41.2%) followed by antimicrobial agents (37.7%) and insulin (7.4%). Conclusion: In this study, at least one-fifth of the patients attending to ED experienced medication errors resulting from multiple factors. More common prescription errors happened during ordering drug dose and frequency. More common administration errors included dug omission or unauthorized drug.